Phase-transfer catalyzed SRN1 reactions for the construction of vicinal quaternary carbon-carbon bonds - Yao, Zhen (2018)
This thesis describes our explorations on phase-transfer catalyzed nucleophilic radical substitution (SRN1) reactions to construct vicinal quaternary carbon-carbon bonds, which cannot be easily accessed by other methods. Up to now, most enantioselective organic radical reactions are conducted under photo conditions; herein we demonstrated that by employing phase-transfer catalysts, enantioselective formation of two vicinal quaternary carbon centers can be achieved. In chapter 1, background information of this thesis is presented. First, a short literature review on phase-transfer catalysis including the development of different types of phase-transfer catalysts and the development of different types of reactions under phase-transfer catalysis is introduced. Second, the methods for the construction of vicinal quaternary carbon-carbon bonds are discussed. Some important natural products containing vicinal quaternary carbon-carbon bonds are also presented, which highlights the importance for the methodology development of this area. Third, the history, mechanism and recent development on nucleophilic radical substitution reactions (SRN1 reactions) are introduced. Last, a short conclusion will be given based on the information above. In chapter 2, a novel phase-transfer catalyzed enantioselective SRN1 reaction between β-cyano ester derivatives and α-bromo-nitroalkanes is developed. This reaction features the carbon-carbon bond formation between two quaternary carbons. By employing novel phase-transfer catalysts developed in our laboratory, this carbon-carbon bond formation can be achieved in an enantioselective way. The mechanism of this reaction is also discussed in the last part. In chapter 3, another nucleophilic radical substitution reaction is presented. The reaction is between methyl 1-oxo-2, 3-dihydro-1H-indene-2-carboxylate and 2-bromo-2-nitropropane. This reaction features an in situ generated electron donor using phase-transfer catalysis to form two vicinal quaternary carbon centers. Although the results of this reaction are not satisfactory at this moment, it serves as a foundation for future development of methods for the construction of two vicinal quaternary carbon centers.